El contexto quirúrgico transoperatorio. Apreciaciones de un grupo de pacientes y del equipo de enfermería (2012)
ABSTRACT: To interpret the experience of being unconscious or alert from a group of patients during the surgical act and appreciations from the members of the nursing team on the same context. Methodology. Qualitative study focusing on grounded theory. Information was collected through a) observation and b) interviews to 20 patients, 19 nursing aides, and 8 nursing professionals who work in level II surgical centers in Valle de Aburrá, Colombia. Results. From being aware of everything to being at the mercy of another, during the intraoperative, the patient goes through different states of conscience, which means being subjected to total care. Instead, for the nursing personnel the same context implies different behavior going between two environments: the “scenario” –when in front of the patient awake, which involves measured and diplomatic behavior; or, “behind the scenes” – with the person under the effects of anesthesia – the behavior is more free and uninhibited. Conclusion. The intraoperative surgical context is different for patients and for the nursing team. However, it is necessary to bear in mind that they are caring for a human being who requires respect, dignified treatment, and that care must be promoted under an ethical perspective.